Kejadian Reaksi Obat yang Tidak Diinginkan Asidosis Tubulus Ginjal Pada Penggunaan Ibuprofen Sebagai Obat Over the Counter - Alifah, Ghina Nur; Pardilawati, Citra Yuliyanda; Kurniawati, Evi; Sukohar, Asep (CV. Jasa Sukses Abadi, 2024)
Ibuprofen is an analgesic drug that can be obtained easily by patients because it is an over the counter (OTC) drug. Ibuprofen when used can risk the lives of patients who consume it incorrectly. Ibuprofen is a drug that causes damage to the kidneys or is nephrotoxic. In large doses ibuprofen has been reported to cause hypokalemia, rhabdomyolysis and renal tubular acidosis Article searches with data sources from either journals or books with keywords used to facilitate searches. Journal articles used through case reports collect case reports of renal tubular acidosis due to the use of ibuprofen. In some of the case reports found, the use of ibuprofen had exceeded the dose set for OTC treatment. Patients with an average age of 41 years and reports ranged in age from 33 years to 63 years. Female patients has dominated the reported cases. The use of ibuprofen that caused the adverse drug reaction event belongs to type C, which is Chronic for continuous and long-term use of the drug. Non-pharmacological therapy that can be done is diet by limiting acid-producing foods and increasing alkaline-producing foods. Handling carried out on patients can be in the form of fluid resuscitation, electrolyte replacement through alkaline therapy, and supportive therapy according to the patient's clinical condition. Alkaline therapy using NaHCO3 and KHCO3 can be a fluid replacement and correct acidosis and hypokalemia.